Biokonversi Kertas HVS Bekas Menjadi Bioetanol Dengan Variasi Kondisi Hidrolisis Asam Dan Waktu Fermentasi - Wahyu, Pri; Chairul, Chairul; Yelmida, Yelmida (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2019)
Indonesia is one of the largest paper producing and exporting countries in the world. Along with the increasing production of paper, the amount of used paper in the world is increase, and in Indonesia also. Waste paper is a very large source of fiber, if this can be used properly, waste paper can produce bioethanol which is able to overcome the scarcity of fossil fuels. Every kilogram of waste paper can produce 0.28 liter of bioethanol with proper operation condition. The purpose of this study is to see the effect of the pretreatment process, find the best acid hydrolysis parameters, and also to find the optimum fermentation time of used HVS fiber with separate hydrolysis and fermentation (SHF) method. The sequence of this study is; pretreatment with NaOH solution for deinking process, then hydrolysis process with variation of acid concentration 2%, 4%, 6% dan 8% for two hours in variation temperature 120, 130 and 140 oC, and the last is fermentation. In the fermentation process, 1 gram Saccharomyces cerevisiae is added in to the sample and let the fermentation process is occur with time variation 24, 48, 72 and 96 hour. The maximum sugar concentration can produce from the hydrolysis process is 85,53 gr/l with acid concentration 8% and hydrolysis temperature 120 oC. The best time for fermentation is 72 hours with bioethanol produced 4%.Keywords: Bioethanol, fermentation, hydrolysis, Saccharomyces cerevisiae, waste paper.